Membentuk Budaya Organisasi Dalam Mengembangkan Perusahaan - Paramitta, Michelle Bulan; Maharani, Trania; Hermana, Cecep (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research is a qualitative research. The method used in this research is literature study orlibrary research the purpose of this is the collection of data through literature. Companies must have an organizational culture because it is very important to provide direction for each employee in achieving company goals. With the existence of an organizational culture, it will have an impact on the company, namely organizational culture becomes the basis of ethics to shape the desired behavioral character of members so that it can support company performance, increase consistency in work and organizational members feel they have an identity that is a pride and characteristic of the company. One of the ways to build an organizational culture to develop a company is by promoting organizational culture. Socialization is one of the company's ways of communicating with employees about everything related to activities within the company and the culture that exists in the company so that employees can understand as a whole. The process of disseminating organizational culture can be done by 1) selecting prospective employees, 2) placing employees in certain jobs, 3) exploring the field of work, 4) giving awards and evaluating employees, 5) being loyal to the organization, 6) enriching news and events regarding various topics related to organizational culture, and 7) there is recognition and achievement promotions given to employees when they have carried out their duties properly.